2011
DOI: 10.1089/ten.tea.2010.0517
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Effects of Mesenchymal Stem Cells Increase Chondrocyte Proliferation and Matrix Formation

Abstract: Previous studies showed that coculture of primary chondrocytes (PCs) with various sources of multipotent cells results in a higher relative amount of cartilage matrix formation than cultures containing only chondrocytes. The aim of this study was to investigate the mechanism underlying this observation. We used coculture pellet models of human mesenchymal stem cells (hMSCs) and human PCs or bovine PCs (bPCs) and studied the fate and the contribution to cartilage formation of the individual cell populations dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
269
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(295 citation statements)
references
References 56 publications
22
269
2
2
Order By: Relevance
“…Interestingly, a structured co-culture of chondrocytes and MSCs acted to help re-establish a chondrogenic phenotype in the expanded chondrocytes within the chondral layer of the bi-layered constructs. It has been reported that chondrogenically primed MSCs release growth factors and cytokines such as TGF-β3, BMP-2, IGF-1 and FGF-2 [53] and such soluble factors may play a role in enhancing chondrogenesis of chondrocytes co-cultured with MSCs [54][55]. Co-culture of chondrocytes and MSCs has also been shown to enhance proliferation of chondrocytes [54,56], although such a phenomena was not observed in our bi-layered co-culture system.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Interestingly, a structured co-culture of chondrocytes and MSCs acted to help re-establish a chondrogenic phenotype in the expanded chondrocytes within the chondral layer of the bi-layered constructs. It has been reported that chondrogenically primed MSCs release growth factors and cytokines such as TGF-β3, BMP-2, IGF-1 and FGF-2 [53] and such soluble factors may play a role in enhancing chondrogenesis of chondrocytes co-cultured with MSCs [54][55]. Co-culture of chondrocytes and MSCs has also been shown to enhance proliferation of chondrocytes [54,56], although such a phenomena was not observed in our bi-layered co-culture system.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that chondrogenically primed MSCs release growth factors and cytokines such as TGF-β3, BMP-2, IGF-1 and FGF-2 [53] and such soluble factors may play a role in enhancing chondrogenesis of chondrocytes co-cultured with MSCs [54][55]. Co-culture of chondrocytes and MSCs has also been shown to enhance proliferation of chondrocytes [54,56], although such a phenomena was not observed in our bi-layered co-culture system. Direct cell to cell interaction may be required to drive the enhanced proliferation of chondrocytes when cocultured with MSCs [56], which is absent in our culture model as cells are separately encapsulated in the different regions of the hydrogel.…”
Section: Discussionmentioning
confidence: 54%
“…This observation underlines the importance of the progenitor cell's trophic role in tissue regeneration. Trophic factors can mediate tissue regeneration in both direct and indirect manners (23)(24)(25). Progressive insight indicates that current culture and treatment protocols allow progenitor cells to contribute mainly to regenerative effects via trophic roles rather than direct tissue formation (26).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings from previous micromass investigations, which indicated that upon coculture, articular chondrocytes were responsible for matrix production as opposed to MSCs in cocultures of adult human bone marrow MSCs with articular chondrocytes from both human and bovine sources. 46,48,58 Among the coculture constructs, a pronounced difference in the cellularity or ECM content was never observed between the 1:3 and 1:5 coculture groups, regardless of culture duration or initial seeding density. As the original objective was to produce a construct laden with cartilage-like ECM, while reducing the number of chondrocytes necessary to do so, these results suggest that ultimately, constructs with 1:5 coculture ratio, and thus, fewer chondrocytes might result in a similar ability to direct cartilage repair as constructs generated with 1:3 cocultures.…”
Section: Cell-derived Pcl/ecm Scaffolds For Cartilage Regeneration Pmentioning
confidence: 95%